Research on 3D geological modeling of fractured-vuggy carbonate reservoirs. (September 2022) - Yan, Lingling; Liu, Quanwen; Liu, Xuefen
Abstract: Fractured-vuggy carbonate reservoirs are mainly composed of holes, caves, and fractures, with large disparity in scale, irregular shape, and discontinuous distribution. Quantitatively depicting the distribution of holes, caves, and fractures in three-dimensional space has always been a technical problem in the development of this type of reservoir, and there is currently no effective geological modeling method. Taking the Yijianfang Formation in the Halahatang area of the Tarim Basin as an example, this paper proposes to model the cavities and fractures separately. The hole model is generated by seismic resampling, and the attribute model uses the inverted porosity as the data volume combined with dynamic and static data constraints to simulate and generate. There are two main methods for fracture modeling. One is deterministic fracture modeling, which is mainly for large-scale fractures; the other is random fracture modeling, which is mainly for small-scale fractures. The deterministic fracture modeling method is based on the seismic data, by extracting the fracture slices of the seismic ant body data, combining the fracture characterization results, screening the fractures, and finally generating a large-scale fracture network; finally integrating hole, the hole model and fracture attributes model to establish a geological model of fracture-cavity reservoirs. Model the cavities and fractures separately was used to drill well Pro1 in yijianfang Formation, revealing that the target zone was 28 meters, and the high yield oil flow was obtained by sidetracking the high point target, which proved that the simulation results were credible.